Efforts to Improve Learning Outcomes in the Main Material of Buffer Solutions Using a Science Literacy-Based Guided Inquiry Model - Juwairiah binti m chaidir (Universitas Lampung, 2021)
This study aims to see the increase in learning outcomes on the subject matter of the buffer using a literacy-based model in class XI SMA Eria Medan. The study population was all students of class XI MIA SMA Eria Medan, namely nine classes. Each class of students. The sampling technique in this study was purposive sampling. The sample chosen was class XI MIA 2 as an experimental class treated with a science literacy-based inquiry model and class XI MIA 6 as a control class treated with conventional models, namely lectures and questions and answers. This study uses test and non-test instruments that have been tested and have been valid. Firstly, the learning outcome data were tested for normality and homogeneity, where the results were obtained by both groups of samples are homogeneous and normally distributed. Hypothesis testing is carried out using the t-test of one party, namely the right side, with the results of this study at a significance level of 4% (α = 0.04) indicating that tcount ttable (5.0573 1.8568) then Ho is rejected. Thus, it shows that there is an effect of guided inquiry learning models based on scientific literacy on learning outcomes. The walking test was carried out to see the relationship between student activity and student learning outcomes. The results showed that tcount ttable (0.582 0.294) then H0 was rejected. Thus, a significant display between student activities and student learning outcomes in the guided inquiry learning model based on scientific literacy. The contribution of student activities to the improvement of student learning outcomes in the experimental class was 42.8%.Keywords: Learning Outcomes, Student Activities, Guided Inquiry, Science Literacy, Buffer Solutions